2017
DOI: 10.1002/ange.201705153
|View full text |Cite
|
Sign up to set email alerts
|

Borylene: eine aufstrebende Verbindungsklasse

Abstract: Freie Borylene (R‐B:) konnten bislang lediglich spektroskopisch in der Gasphase oder in Tieftemperatur‐Matrices charakterisiert werden. In der letzten Zeit gelang es jedoch, einige Mono‐ und Di(Lewis‐Base)‐stabilisierte Borylene zu isolieren. In beiden Verbindungen ist das Boratom durch die formale Oxidationsstufe +I gekennzeichnet, während es sich in klassischen Organoborverbindungen in der Oxidationsstufe +III befindet. Mono(Lewis‐Base)‐stabilisierte Borylene sind isoelektronisch zu Singulett‐Carbenen, und i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“…Chemie and B(C 6 F 5 ) 3 , [13] which is surprisingly sensitive towards N 2 loss even at room temperature,c ontrasting the behavior of (Ph 3 P) 2 N 2 .T his finding clearly shows that judicious choice of Lewis acids and bases offers are ap otential avenue to metal-free capture of N 2 . Against conventional wisdom, hypovalent boron species, namely borylenes R-B with am onovalent boron center, [14] possess alone pair (LP) of electrons in combination with two unoccupied orbitals at boron, asituation mimicking TMs with filled and empty metal-centered dorbitals.Borylenes must be stabilized by one or two Lewis donors (L), such as Nheterocyclic carbenes (NHCs), cyclic alkyl amino carbenes (CAACs), [8b] and CO,orinthe coordination sphere of aTM. This allows judicious adjustment of the energy of the orbitals on boron and therefore opens the door for the challenging task of nitrogen fixation (Scheme 2, right).…”
Section: Methodsmentioning
confidence: 99%
“…Chemie and B(C 6 F 5 ) 3 , [13] which is surprisingly sensitive towards N 2 loss even at room temperature,c ontrasting the behavior of (Ph 3 P) 2 N 2 .T his finding clearly shows that judicious choice of Lewis acids and bases offers are ap otential avenue to metal-free capture of N 2 . Against conventional wisdom, hypovalent boron species, namely borylenes R-B with am onovalent boron center, [14] possess alone pair (LP) of electrons in combination with two unoccupied orbitals at boron, asituation mimicking TMs with filled and empty metal-centered dorbitals.Borylenes must be stabilized by one or two Lewis donors (L), such as Nheterocyclic carbenes (NHCs), cyclic alkyl amino carbenes (CAACs), [8b] and CO,orinthe coordination sphere of aTM. This allows judicious adjustment of the energy of the orbitals on boron and therefore opens the door for the challenging task of nitrogen fixation (Scheme 2, right).…”
Section: Methodsmentioning
confidence: 99%
“…The first stable metal‐free borylene, synthesized in 2010 by Bertrand, [11] relied on the electronic and steric stabilization of two cyclic alkyl(amino)carbene (CAAC) ligands, acting as strong σ donors and π acceptors, [12,13] and thus enabling the delocalization of the excess electron density over the entire CAAC−B−CAAC π framework. Since then, numerous symmetrical and unsymmetrical tricoordinate borylene derivatives (LL′BR, L,L′=neutral donor ligands) with various R substituents (e. g., H, F, Cl, Br, CN, NCS, aryl, boryl) have been isolated [14,15] . Their reactivity, however, remains often hampered by excessive steric hindrance around the tricoordinate boron center.…”
Section: Introductionmentioning
confidence: 99%
“…The last two decades have witnessed a surge in the use of carbenes, notably N‐heterocyclic carbenes (NHCs) and cyclic (alkyl)(amino)carbenes (CAACs), as stabilizing ligands in the synthesis of low‐valent boron species [33–34] . While monoboranes and diboranes(4) have proven to be versatile building blocks for novel chemical compounds, [35–36] very little is known about electron‐precise oligoboranes (B 3 −B 6 ) due to the lack of reliable supporting ligands during the course of functionalization and the synthetic difficulties associated with their precursors [25,37–38] . Early work by Nöth and coworkers demonstrated that halogenation of tetraboranes could be achieved to give a variety of dihalotetraboranes (B 4 X 2 R 4 ), which showed promise as candidates for more complex structures [25] .…”
Section: Introductionmentioning
confidence: 99%